Factors associated with breastfeeding duration: a prospective cohort study in Sichuan Province, China - Tang, L.; Lee, A.; Binns, Colin (Institute of Pediatrics of Zhejiang University, 2014)
Background: The World Health Organization (WHO) recommends exclusive breastfeeding for 6 months and continued breastfeeding thereafter with appropriate complementary foods for at least 2 years or longer. This study aimed to determine the factors associated with breastfeeding duration in Sichuan Province of China. Methods: A prospective longitudinal study of 695 women, with a follow-up response rate of 71.9%, was conducted in Jiangyou, Sichuan Province in the period of 2010–2011. Participants were interviewed at discharge and followed up by telephone at 1, 3, 6 and 12 months postpartum. Breastfeeding duration was estimated by the Kaplan-Meier method. Cox regression analyses were performed to identify factors associated with the breastfeeding duration. Results: The median duration of “any breastfeeding” was 8.0 [95% confidence interval (CI): 7.8, 8.2] months. Maternal age less than 25 years [adjusted hazard ratio (HR): 1.61; 95% CI: 1.32, 1.96] and maternal return to work before 6 months postpartum (adjusted HR: 1.69; 95% CI: 1.32, 2.17) were associated with a shorter duration of breastfeeding. Women who delivered at hospital (adjusted HR: 1.33; 95% CI: 1.05, 1.67), introduced solid foods (adjusted HR: 1.30; 95% CI: 1.02, 1.64) and intended to stop breastfeeding within 6 months, or undecided how long to breastfeed (adjusted HR: 1.41; 95% CI: 1.16, 1.72), were more likely to terminate lactation within 1 year. Conclusions: The duration of breastfeeding in Jiangyou was far below the recommendation of the WHO. Education programs targeting vulnerable subgroups of mothers should be provided in Sichuan to help them maintain breastfeeding as long as possible.